Duvalius (Duvalius) lencinai Mateu & Ortuño, 2006 (Coleoptera, Carabidae, Trechini) una especie hipogea del sur de la península ibérica. Morfología, reubicación taxonómica, sistemática y biología - Ortuño, V. M. (Animal Biodiversity and Conservation, 2013)
Duvalius (Duvalius) lencinai Mateu & Ortuño, 2006 (Coleoptera, Carabidae, Trechini) a hypogean species from the south of the Iberian peninsula. Morphology, new taxonomic placement, systematics and biology Duvalius (Duvalius) lencinai Mateu & Ortuño, 2006 was discovered in two new localities in the municipal district of Siles (Jaen, Spain): Sima Curva del Espino and Sima de los 30 Años, approximately 10 and 17 km, respectively, away from the type locality. The study of several individuals through dissection and use of optic and electronic microscopic preparations has increased the knowledge of the anatomy of this species. Evagination of the internal sac allowed further study of the sclerotized structures and led to the proposal of a new placement for this species within the genus Trechus Clairville 1806: Trechus (Trechus) lencinai (Mateu & Ortuño, 2006) n. comb. Although it comprises characters of the T. fulvus group and the T. pyrenaeus group, the endophallus is more similar to several species of the T. quadristriatus group and the T. tingitanus group. It could not therefore be placed in any of the species groups proposed by Jeannel. Some data about its biology (temporal and spatial distribution) and accompanying arthropod fauna are given.